Comparison of the Functional Health Limitations of Veterans Deployed to Iraq or Afghanistan to Veterans Deployed to Desert Shield/Storm With Chronic Fatigue Syndrome. (2nd July 2016) - McAndrew, Lisa M.; Chandler, Helena K.; Serrador, Jorge M.; Quigley, Karen S.; H. Natelson, Benjamin; Lange, Gudrun
ABSTRACT: The majority of studies to examine the levels of physical symptoms after Operation Enduring Freedom/Operation Iraqi Freedom (OEF/OIF) deployment have found that veterans experience high levels of physical symptoms after deployment. What is not known is whether the physical symptoms experienced by OEF/OIF veterans meet criteria for chronic fatigue syndrome (CFS), as was seen after Operation Desert Shield/Operation Desert Storm. This determination would require a medical evaluation to rule out medical conditions that may explain the symptoms. Further, it is not well known if the physical symptoms experienced by OEF/OIF veterans are causing significant functional impairment. We compared OEF/OIF veterans with CFS to Desert Shield/Storm veterans with CFS seen at a postdeployment Veterans Affairs (VA) clinic soon after their respective deployments. We found 17.6% of OEF/OIF veterans met criteria for CFS. Compared to Desert Shield/Desert Storm veterans with CFS, the OEF/OIF veterans with CFS demonstrated poorer mental health function and similar physical health function.